2014
DOI: 10.1089/humc.2013.208
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Systemic rAAV9-hNAGLU Delivery for Treating Mucopolysaccharidosis IIIB: Toxicology, Biodistribution, and Immunological Assessments in Primates

Abstract: No treatment is currently available for mucopolysaccharidosis (MPS) IIIB, a neuropathic lysosomal storage disease caused by autosomal recessive defect in a-N-acetylglucosaminidase (NAGLU). In anticipation of a clinical gene therapy treatment for MPS IIIB in humans, we tested the rAAV9-CMV-hNAGLU vector administration to cynomolgus monkeys (n = 8) at 1E13 vg/kg or 2E13 vg/kg via intravenous injection. No adverse events or detectable toxicity occurred over a 6-month period. Gene delivery resulted in persistent g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 47 publications
9
82
0
1
Order By: Relevance
“…After a single systemic gene delivery of rAAV9 in non-human primates, pre-existing anti-AAV9 antibody at low level did not diminish vector transduction. However, high level pre-existing anti-AAV9 antibody leds to the reduction of vector transduction in somatic tissues, but had less impact on transduction in the CNS, indicating that CNS entry is less sensitive to pre-existing anti-AAV9 antibody [82]. These studies led to use of AAV antibody titer as a criterion of MPS patient eligibility to enter clinical trials of gene therapy.…”
Section: Pre-clinical Study Of Gene Therapy For Mpsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a single systemic gene delivery of rAAV9 in non-human primates, pre-existing anti-AAV9 antibody at low level did not diminish vector transduction. However, high level pre-existing anti-AAV9 antibody leds to the reduction of vector transduction in somatic tissues, but had less impact on transduction in the CNS, indicating that CNS entry is less sensitive to pre-existing anti-AAV9 antibody [82]. These studies led to use of AAV antibody titer as a criterion of MPS patient eligibility to enter clinical trials of gene therapy.…”
Section: Pre-clinical Study Of Gene Therapy For Mpsmentioning
confidence: 99%
“…Several studies have shown that systemic delivery of rAAV8 or rAAV9 containing the deficient gene cause elevation of lysosomal enzyme activity in CNS lesions and correction of disease progression in mouse models of MPS IIIA [9093] and MPS IIIB [82,9496]. Fu et al showed that a single IV administration of a scAAV9 vector encoding human N-sulfoglucosamine sulfohydrolase (hSGSH) (5e 12 vg/kg) in an MPS IIIA model mouse significantly improved behavior performance and survival rate [93] Improvements were best when the vector was administered at an early stage of disease, but these phenotypes were also partially corrected when treatment was delayed until mice showed intermediate progression of disease.…”
Section: Pre-clinical Study Of Gene Therapy For Mpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most likely the answer is that it will depend on the neurological disease and therapeutic mechanism. For instance, in LSDs where the entire CNS is involved, the ideal approach is to have dispersed expression of the missing lysosomal enzymes by systemic delivery of AAV9 vectors [128,129]. Some degree of enzyme overexpression will be required to drive its secretion and uptake in non-transduced cells for correction of the lysosomal storage phenotype.…”
Section: Challengesmentioning
confidence: 99%
“…В недавних исследованиях на экспериментальных животных была показана возможность непосредствен-ной трансдукции клеток ЦНС и, соответственно, повы-шения активности фермента в клетках головного мозга при внутривенном введении аденоассоциированного вирусного вектора серотипа 9 (AAV9), экспрессирующего фермент ␣-N-ацетилглюкозаминидазу, дефицит которого приводит к развитию МПС IIIB [39].…”
Section: генная терапия In Vivounclassified